2012
DOI: 10.1128/iai.00441-12
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Inhibition of Chlamydia trachomatis Infection in Epithelial Cells Due to Stimulation of P2X 4 Receptors

Abstract: Bacterial infections of the mucosal epithelium are a major cause of human disease. The prolonged presence of microbial pathogens stimulates inflammation of the local tissues, which leads to changes in the molecular composition of the extracellular milieu. A well-characterized molecule that is released to the extracellular milieu by stressed or infected cells is extracellular ATP and its ecto-enzymatic degradation products, which function as signaling molecules through ligation of purinergic receptors. There ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 65 publications
1
20
0
Order By: Relevance
“…Similar to other studies, despite differences at the mRNA levels, we could detect protein expression for all four adenosine receptors (Giacomelli et al, 2018). Lung epithelial cells are also known to express P2 purinergic receptors that respond to ADP and/or ATP (Burnstock et al, 2012) and ATP and/or ADP impaired replication of Chlamydia trachomatis in cervical epithelial cells (Pettengill et al, 2012). However, addition of ATP did not alter S. pneumoniae binding to the lung epithelial cells in vitro while AMP significantly decreased bacterial binding.…”
Section: Figuresupporting
confidence: 86%
See 1 more Smart Citation
“…Similar to other studies, despite differences at the mRNA levels, we could detect protein expression for all four adenosine receptors (Giacomelli et al, 2018). Lung epithelial cells are also known to express P2 purinergic receptors that respond to ADP and/or ATP (Burnstock et al, 2012) and ATP and/or ADP impaired replication of Chlamydia trachomatis in cervical epithelial cells (Pettengill et al, 2012). However, addition of ATP did not alter S. pneumoniae binding to the lung epithelial cells in vitro while AMP significantly decreased bacterial binding.…”
Section: Figuresupporting
confidence: 86%
“…We found that consistent with previous studies with A549 cells, a type II pneumocyte cell line (Roman et al, 2006) as well as primary bronchial epithelial cells (Zhong et al, 2006), H292 cells expressed mRNA for A2B, A1, A2A, and A3 in decreasing levels. Lung epithelial cells are also known to express P2 purinergic receptors that respond to ADP and/or ATP (Burnstock et al, 2012) and ATP and/or ADP impaired replication of Chlamydia trachomatis in cervical epithelial cells (Pettengill et al, 2012). Lung epithelial cells are also known to express P2 purinergic receptors that respond to ADP and/or ATP (Burnstock et al, 2012) and ATP and/or ADP impaired replication of Chlamydia trachomatis in cervical epithelial cells (Pettengill et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although not the subject of the current study, it is also possible that P2X4Rs can also increase, at least under some circumstances, the killing of obligate intracellular bacteria. In fact, Pettengill et al reported that P2X4Rs augmented the killing of Chlamidia trachomatis (C. trachomatis) in epithelial cells (45). However, based on .…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest a key role for this receptor in the elimination process. Previous studies have shown the ability of infecting pathogens to cause ATP release in a physiological form (22,23). Thus, we measured the ATP release during infection with L. amazonensis at different time points.…”
Section: P2x7 Receptor Is Involved In L Amazonensis Elimination Medimentioning
confidence: 99%